Effects of removing albumins and globulins on the thermal stability, food quality and starch digestibility of α-amylase hydrolyzed rice flour - Qin Feng; Muxin Feng; Ying Peng; Ying Yang; Ruoyi Wang; Jianhua Wan; Jinhua Liu; Wenfang Han (Food Chemistry: X)
Instant rice flour products are usually produced by hydrolyzing rice flour using α-amylase. As albumins and globulins are major allergenic proteins in rice flour, the effects of removing albumins and globulins on the thermal stability, food quality and starch digestibility of α-amylase hydrolyzed rice flour of three varieties (FHs including F1H, F2H and F3H) were studied. The removal of albumins and globulins changed the maltose and glucose content of FHs, promoted the rearrangement of starch molecules to different degrees of retrogradation in them, improved their starch digestibility without negatively affecting their reconstituability and sensory quality, and increased the digestive rate of F1H to 82.98 % and the slowly digestible starch content of F3H to 48.44 %. Thus, the removal of albumins and globulins is an effective approach to reduce the allergenicity and improve the quality of FHs, which provides a basis for developing high-quality instant rice flour products with lower allergenicity.